The sex-related discrepancy in laboratory parameters of severe COVID-19 patients with diabetes: A retrospective cohort study - Hammad, Maha O. (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2021)
• There is a sex-disparity in laboratory data of severe COVID-19 patients with diabetes. • Males showed higher ALT and CRP; whereas females showed higher lymphocytes and MPV. • Males with severe COVID-19 and diabetes tend to have higher MPVLR and CAR. • Diabetic males tend to experience higher inflammatory burden than females. • Sex variable impacts the clinical outcome of severe COVID-19 patients with diabetes.